Analysis of “Virtual Family” Influencers Operational Strategies on Douyin in China: A Case Study of “Sharing Daily Life with Daughter” - Xiang, Juan (International Theory and Practice in Humanities and Social Sciences, 2025)
In recent years, the phenomenon of “Kinship Disconnection” among young people has triggered heated discussions. In the process of “Kinship Disconnection”, young people are keen on “Kinship Recognition” in the virtual world, and establishing new kinship relationships with “Virtual Family”. This study, employing content analysis, conducts an in-depth examination of 147 short videos posted by the “Sharing Daily Life with Daughter” Douyin account from September 13, 2023, to October 22, 2024, aiming to explore the operational strategies of “Virtual Family” influencers. The findings reveal that, in terms of content, identity construction, and emotional value are provided through the presentation of warm and loving parental images, immersive scenarios, and diversified video production methods; in terms of users, the viewing group is dominated by females aged 18-30 years old, and there are more negative tendencies in the comment section, with fewer interactions with bloggers; in terms of business, advertisement implantation is the main profit-making method. Further analysis shows that the emotional engagement and commercial strategies of “Virtual Family” influencers are closely intertwined. Influencers attract attention by offering emotional support and psychological comfort, thereby establishing an audience base for advertising placement and achieving commercial monetization. However, this operational model is fraught with challenges, such as trust issues, media dependency, and audience commodification. While virtual family influencers can partially fulfill emotional substitution needs, the potential risks they entail warrant careful consideration.